The surrogate mothers: free and altruistic women - Einarsdóttir, Jónína; Finnsdóttir, Helga (Stjórnsýslustofnun, 2013)
The aim of this article is to describe the results of research on surrogate mothers and how they are presented in Icelandic mass media and by individuals who are concerned with surrogacy. Data was collected with participation observation, interviews and analyses of public discussions. Most of the interviewees and participants in meetings and seminars on surrogacy took stance either for or against a parliamentary proposition to legalize surrogacy in Iceland. Supporters argued that women should be free to decide whether they want to become surrogate mothers, however without being paid. They praised altruistic women who give infertile couples the true gift, a child, and argued that according to research, surrogacy was successfully implemented in the Western world. They maintained that legalization would impede exploitation of women in low-income countries. Opponents of legalization argued that nobody should have the right to use other’s body for own gain, with or without payment. They feared that legalization would normalize surrogacy and force women to become surrogate mothers. Still, some did not take a stance but argued that surrogacy needed to be carefully discussed prior to legislation, and they called for additional research. Researchers complain about lack of long-term research on the consequences of surrogacy on women, their experiences of surrogacy, conditions and wellbeing and that most available research is based on small sample sizes. Still, there is evidence that demand for the services of Indian surrogate mothers has increased from countries that have legalized surrogacy. Markmið þessarar greinar er að lýsa niðurstöðum rannsókna á staðgöngumæðrum og hugmyndum íslenskra fjölmiðla og áhugafólks um staðgöngumæðrun um konur sem taka að sér að ganga með barn fyrir aðra. Gagnaöflun fór fram með þátttökunálgun á opnum málstofum og fundum um staðgöngumæðrun, viðtölum við einstaklinga sem hafa látið sig málið varða og greiningu á opinberri umræðu. Viðmælendur og þátttakendur á málstofum skiptu sér flestir í ...